Relationship Between the Level of Community Knowledge About Dengue Hemorrhagic Fever and Larvae of Aedes aegypti Examination in Deli Serdang Regency, North Sumatra, Indonesia - Rambe, Ismatul Fauziah; Andina, Meizly; Nurfadly, - (International Journal of Human and Health Sciences (IJHHS), 2018)
Dengue hemorrhagic fever is one of the major public health problems in the world. This disease that is transmitted through Aedes aegypti mosquitoes is classified as dangerous because it can cause dengue shock syndrome. Its spread can attack anyone, anywhere and can be several people at the same time resulting in this disease has a fairly high incidence rate, especially in tropical climates such as Indonesia. The most effective prevention is breaking the chain of transmission of DHF. This termination is done by preventing larvae found in their breeding places from developing into adult mosquitoes. Objective: to determine the relationship of the level of public knowledge about Dengue Hemorrhagic Syndrome (DHF) with the presence of Aedes aegypti mosquito larvae in Deli Serdang Regency, North Sumatra, Indonesia. Materials and Methods: This is a crosssectional analytic study used quota sampling method with a total of 78 samples. Results and Discussion: this study shows that the highest level of knowledge from respondents is enough as many as 38 people (48.7%). The houses that were found to have positive larvae containers were 26 houses (33.3%) and the most were located outside the house were 15 (19.2%). Chi-square results showed P-value = 0.984. Conclusion: There is no correlation between the levels of community knowledge about DHF with the presence of Aedes aegypti mosquito larvae. International Journal of Human and Health Sciences Vol. 03 No. 01 January’19. Page : 19-22